EFFICIENCY OF MEDICATIONS WITH PROBIOTIC POTENCY IN THE PROCESS OF PROSTHODONTIC TREATMENT WITH WHOLE PIECE PERMANENT STRUCTURES OF DENTAL PROSTHESES OF PATIENTS WITH DIABETES MELLITUS TYPE 2 - Ovcharenko, E. N.; Zadko, S. I.; Kharchenko, V. Z.; Severinova, S. K.; Lavrovskaya, O. M.; Irza, O. L.; Lavrovskaya, Ya. A. (Zhurnal Grodnenskogo gosudarstvennogo medit͡s︡inskogo universiteta, 2019)
Background. Dental health in patients with diabetes mellitus type 2 and methods of its correction is an important part in the complex of medical and preventive care of the pathology. Objective. The objective of the research is to study the efficiency of medications with probiotic potency in the process of prosthodontic treatment with whole piece permanent structures of dental prostheses of patients with diabetes mellitus type 2. Material and мethods. Qualitative and quantitative characteristics of oral fluid microbiocenosis of patients with diabetes mellitus type 2 have been studied in the process of the combination treatment including denture treatment with whole piece permanent structures with the use of «Bifidumbacterinum». Bacterial inoculation for oral fluid was done using Gould serial delution method. Results. Progressive reduction in the quantification which marks the content of pathogenic and liable to be pathogenic organisms in patients with diabetes mellitus type 2 stoma was noted after the combination treatment had been done. Herewith, the significance of stabilizing flora agents increased. Conclusions. The results of the microbiological research presented prove applicability of bacterial medication along with a package of measures during oral rehabilitation of patients with diabetes mallitus type 2 .